PENGARUH SERVICESCAPE TERHADAP KEPUTUSAN BERKUNJUNG WISATAWAN NUSANTARA DI MUSEUM PERUNDINGAN LINGGARJATI - Anggraeni, Widya (2014)
Asia tourist developments in the world's are growing faster especially in Asia Pacific. This is a positive impact on the development of tourism in Indonesia because of tourism growth in 2013 exceeded the number of global tourism. Bali Declaration dated July 14, 2000 on conserving Cultural Heritage for Sustainable Social, Economic and Tourism Development, stated that the culture and heritage of Indonesian tourism is an excellent product. One of the provinces in Indonesia which is favoring the museum as a tourist potential is West Java. Historical tourist destination being developed by Departement Tourism and Culture Kuningan is Museum Perundingan Linggarjati. In the year 2013 the number of visits decreased Museum Perundingan Linggarjati not achieving the target, because an expected visit. One of the efforts made to improve the museum's decision to visit the servicescape strategy. Variables independent of this study is the servicescape (X) which consists of a sub-variable ambient factors, design factors, and social factors. Dependent variable is the decision to visit (Y) consisting of product selection, brand selection, the selection purchasing channels, the timing of visits and number of visits elections. This type of research is descriptive and verification, and the method used is explanatory survey sampling technique is systematic random sampling. Objects in this study is that domestic tourists who visit the Museum Perundingan Linggarjati, with a sample size of 100 respondents. Data analysis techniques used multiple linear regression using SPSS Windows 20. These results indicate that the sub-variables that have the highest influence is a social factor that has the most impact and low is the design factor. As for the recommendation to the manager of the museum talks Linggarjati in improving decisions and the visit is to optimize employee performance and increase understanding of the physical environment, especially the application of servicescape strategy